Theological anthropology in interreligious perspective - Demiri, Lejla; Zaman, Mujadad; Winter, Tim; Schwöbel, Christoph; Bodrov, Alekseĭ (Sapientia Islamica, 2022)
Die Autoren des vorliegenden Bandes setzen sich mit islamischen und christlichen Vorstellungen vom menschlichen Leben auseinander. Auf der Grundlage klassischer und zeitgenössischer theologischer Fragen und Interessen bieten sie der geistes- und naturwissenschaftlichen Forschung wichtige Einblicke in Debatten über den Menschen, sein Wesen, seine Zukunft und seine Ziele.InhaltsübersichtTim Winter: Introduction Part I: Created in the Image: Human Wholeness Christoph Schwöbel: 'Theology ... defines the whole and complete and perfect human being.' Being Human in the Dispute between Theology and Philosophy: Variations on a Christian, Muslim and Jewish Theme – Recep Şentürk Multiplex Human Ontology and Multiplex Self: An Alternative Understanding of Human Behaviour Part II: Death and Human Becoming Ivana Noble: Created to Be and to Become Human: A Christian Perspective – Lejla Demiri: 'He Who has created death and life' (Q 67:2): Death in Islamic Theology and Spirituality Part III: Belief and Devotion Ruggero Vimercati Sanseverino: 'The Prophet is closer to the believers than they are to themselves' (Q 33:6): A Scriptural Inquiry into the Anthropological Foundation of the Ittibā ʿ al-Nabī (Sequela Prophetae) – Amina Nawaz: Mutual Influences of Christian and Muslim Anthropologies in History: A Case Study of Sixteenth-Century Morisco Devotions Part IV: The Child in Human Becoming Friedrich Schweitzer: The Anthropology of the Child: Opportunities and Challenges for a Neglected Topic in Christian-Muslim Dialogue – Mujadad Zaman: Children in the Medieval Islamic Imagination: A Path Towards Pedagogic Dialogue Part V: Dignity and Sinfulness Daniel A. Madigan SJ: 'These people have no grasp of God's true measure' (Q 39:67): Does the Doctrine of Original Sin do Justice to God and to Humanity? – Ralf K. Wüstenberg: The 'Fall' of Mankind: Structural Parallels between the Narratives of Sin in Christianity and Islam Part VI: Limits to Being, Limits to Naming God Simone Dario Nardella: God, Man, Being: ʿAbd al-Ghanī al-Nābulusī's Explanation of the Intellect's Capacity to Know God in al-Wujūd al-Ḥaqq – Paul-A. Hardy: On Naming and Silencing – Conor Cunningham: Thomas Aquinas' Anthropology: Stuck in the Middle with You Part VII: Futures Michael Kirwan SJ/Ahmad Achtar: 'The wound where light enters': A 'Common Word' for Being Human in Islam and Christianity